Contemporary issues in business, economics and finance - Grima, Simon; Özen, Ercan; Boz, Hakan (Contemporary studies in economic and financial analysis ;, 2020)
This special edition of Contemporary Studies in Economics and Financial Analysis offers a selection of carefully curated chapters from invited participants in the International Applied Social Science Congress 4-6 April 2019. In these chapters, expert authors tackle issues across a variety of economic and financial disciplines. Chapters include: the role of bankruptcy risk prediction in assuring the financial performance of Romanian industrial capitals; the effects of female employment on economic growth; perceived exchange rates and exchange rate management techniques; the European Union's anti-discrimination laws in sport; bank stability in Latvia; and many more. With vigorous academic rigour, the authors and editors to this volume bring to life a wide variety of economic and financial discussions, from theory to practice. For any financial or economic researcher, student, or practitioner, this is an unmissable volume of research.